Vietnam tourist guidebook - Vietnam National Administration of Tourism (H. The Cultural Information Publishing House, 2005)
Contents: Facts about Vietnam; useful information; culture; Hanoi and the red river delta; north-east coast; far north - east; north-west; north-central Vietnam; central Vietnam; south-central coast; central highlands; Ho Chi Minh city and neighbouring provinces; Mekong delta.
Keywords: Quản trị DV Du lịch và Lữ hành